If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + 3x) = -1x + -19 (1 * 2 + 3x * 2) = -1x + -19 (2 + 6x) = -1x + -19 Reorder the terms: 2 + 6x = -19 + -1x Solving 2 + 6x = -19 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + 6x + x = -19 + -1x + x Combine like terms: 6x + x = 7x 2 + 7x = -19 + -1x + x Combine like terms: -1x + x = 0 2 + 7x = -19 + 0 2 + 7x = -19 Add '-2' to each side of the equation. 2 + -2 + 7x = -19 + -2 Combine like terms: 2 + -2 = 0 0 + 7x = -19 + -2 7x = -19 + -2 Combine like terms: -19 + -2 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| 6+5a=3(1+2a) | | -p-3=11 | | 6p-1=-13+3p | | -3(-2m+3)=1 | | -9t+2t+4t= | | 4s(256/s^2) | | x^2-1000x+2=0 | | 3k-1=7+7k | | n-8-5n-16=n-7-7 | | 6-18n-14n+10= | | 4-x+4x=7+4x | | 2t+2t= | | 7x=5x+9 | | -7a-1=-3-7a | | 16x+2=9x+51 | | -7n-3-6=-10+1+3n-6n | | 2(3)x=3x+1 | | 1-3x=4-3x | | x/8-9=10 | | 2-3v-1=-3-8v+4-15 | | -8+2n=2n-8 | | 0.33h+4=3 | | 0=2/3x | | 3x+4(3x-2)=44 | | 20w^3-15w^2=0 | | m+7-8m=12-8m | | -12+7n=8n-5 | | 1+6x+3-6=5x-6 | | -12=3/4x | | 3-4p-6=-6p+1 | | 10=-19+7 | | 3(t-6)= |